2017
DOI: 10.2967/jnumed.113.122671
|View full text |Cite
|
Sign up to set email alerts
|

First Evaluation of PET-Based Human Biodistribution and Dosimetry of 18F-FAZA, a Tracer for Imaging Tumor Hypoxia

Abstract: 18 F-labeled fluoroazomycinarabinoside ( 18 F-FAZA) is a PET biomarker for noninvasive identification of regional tumor hypoxia. The aim of the present phase I study was to evaluate the biodistribution and dosimetry of 18 F-FAZA in non-small cell lung cancer patients. Methods: Five patients awaiting surgical resection of histologically proven or radiologically suspected non-small cell lung cancer were prospectively enrolled in the study. The patients underwent PET/CT after injection of 371 6 32 MBq of 18 F-FAZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 19 publications
1
49
0
Order By: Relevance
“…The improved hydrophilicity allows for faster clearance from normoxic tissues and a better imaging contrast at earlier time points than FMISO as demonstrated in breast (EMT6) and pancreatic cancer (AR42J) tumors in mice models (Piert et al, 2005 ). Biodistribution studies revealed differences in humans compared to animals where slower clearance from kidneys in humans was observed although still rendered a favorable radiation risk profile for applications in PET imaging (Savi et al, 2017 ). Successful clinical studies have been carried out in glioma (Postema et al, 2009 ), lymphoma (Postema et al, 2009 ), lung (Postema et al, 2009 ; Bollineni et al, 2013 ), head and neck (Grosu et al, 2007 ) or cervical cancers (Schuetz et al, 2010 ).…”
Section: Preclinical and Clinical Imaging Of Hypoxiamentioning
confidence: 99%
“…The improved hydrophilicity allows for faster clearance from normoxic tissues and a better imaging contrast at earlier time points than FMISO as demonstrated in breast (EMT6) and pancreatic cancer (AR42J) tumors in mice models (Piert et al, 2005 ). Biodistribution studies revealed differences in humans compared to animals where slower clearance from kidneys in humans was observed although still rendered a favorable radiation risk profile for applications in PET imaging (Savi et al, 2017 ). Successful clinical studies have been carried out in glioma (Postema et al, 2009 ), lymphoma (Postema et al, 2009 ), lung (Postema et al, 2009 ; Bollineni et al, 2013 ), head and neck (Grosu et al, 2007 ) or cervical cancers (Schuetz et al, 2010 ).…”
Section: Preclinical and Clinical Imaging Of Hypoxiamentioning
confidence: 99%
“…[ 18 F]DiFA had a higher rate of urinary excretion (86.4%) than other hypoxia tracers, such as [ 18 F]FAZA (15% [11]), [ 18 F]FETNIM (60% [15]), and [ 18 F]HX4 (45% at 3.6 h [14]). In general, more hydrophilic compounds will have more rapid biodistribution and clearance from the body [16].…”
Section: Discussionmentioning
confidence: 99%
“…3.1 (PMOD Technologies, Zurich, Switzerland). The uptake of each major organ was calculated by drawing a volume of the region based on the contours of the PET and CT images as described previously [11]. At each time point, the decayed radioactivity of each source organ is expressed as a percentage of the injected activity (%IA) and plotted against time, and fitted to an exponential or sum-of-exponentials function in organ level internal dose assessment/exponential modeling (OLINDA/EXM) 1.1 computer software (Vanderbilt University, Nashville, TN) [12] to determine the total number of disintegrations per unit of administered activity, hereafter referred to as the normalized number of disintegrations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, detection of tumor hypoxia in PET is a direct measurement, presenting higher sensitivity and is directly quantitative. Compared to the more commonly used fluorine-based PET tracers, tracers based on copper allow a rapid visualization of hypoxia (in contrast to [ 18 F]F-MISO), or better penetration of the blood-brain barrier and no urinary bladder uptake (in contrast to [ 18 F]FAZA) [11,12], in addition to longer half-lives that contributes to better image quality and more convenient clinical practice. Here, we focus on reviewing recent advances and challenges in imaging of tumor hypoxia using PET with one of the most promising copper tracers, [ 64 Cu][Cu-diacetyl-bis(N 4methylthiosemicarbazone)] ([ 64 Cu][Cu(ATSM)]), and simple ionic [ 64 Cu]Cu(II) salts, as well as implications on using these tracers for simultaneous internal molecular radiotherapy.…”
Section: Introductionmentioning
confidence: 99%